Implementation of Waste Management Policy in Realizing Environmental Health in Kuningan District: (Study of Kuningan Regency Regional Regulation Number 04 of 2010 concerning Waste Management) - Deni Nurcahya; Kamal Alamsyah; Uyat Suyatna (Pasundan Social Science Development, 2021)
The main problem in this research is that implementing policies on waste management in realizing environmental health in Kuningan Regency has not been implemented optimally. The approach used in this research is the policy implementation theory of Van Meter and Van Horn, namely the stages of size and content of policies, resources, characteristics of implementing organizations, attitudes of policy implementers, communication between implementing organizations, and the social, economic and political environment. The method used in this research is descriptive analysis with a qualitative approach. The descriptive method is used to overview each factor in implementing policies on waste management to achieve environmental health in the Kuningan Regency. At the same time, the qualitative approach was chosen, considering that this approach is expected to obtain accurate data and study research problems in depth so that the expected results can be obtained. Some factors that cause the implementation of the policy on Waste Management in Achieving Environmental Health in Kuningan Regency have not been optimized. This is indicated by the absence of an incentive mechanism for villages/communities to increase the effectiveness/efficiency of public service delivery in the solid waste sector. This egoistic culture develops in the community because there is no clear understanding of the Kuningan Regency Environmental Service officers and the TPST 3R KSM community. As a result, waste management and the budget for waste management usually get the lowest priority weight compared to other programs in creating a clean environment. A strategy was found that could be carried out so that the implementation of policies on Waste Management in Realizing Environmental Health in Kuningan Regency (Study of Kuningan Regency Regional Regulation Number 04 of 2010 concerning Waste Management) runs effectively, namely the condition of waste management and its urgency and accessibility to decision-makers in order to build. The commitment of leaders and appreciation and community participation. In addition, the relatively small institutional financial resources become a synergistic unit through partnership, harmonization, synchronization, mobilization, or collaboration with local governments (provincial and district), related institutions/agencies, and the community.